A Systematic Literature Review of Learning Strategies for Reading Comprehension Skills among Elementary School Students - Putri Hana Pebriana; Muhammad Hidayatul Rama; Restu Arrobbi; Hanati Nikma; Nadya Rewina Putri; Kartika Putri; Aulia Ningsih (The Future of Education Journal, 2026)
Reading comprehension skills are fundamental competencies that play an important role in the learning success of elementary school students. However, various studies indicate that students’ reading comprehension abilities remain relatively low, partly due to the use of less varied and insufficiently student-centered learning strategies. This study aims to systematically examine various learning strategies for reading comprehension skills among elementary school students through the Systematic Literature Review (SLR) method. The research was conducted by reviewing relevant scientific articles from national and international journal databases, which were then selected based on inclusion and exclusion criteria. The data were analyzed using content analysis to identify the types of learning strategies, implementation trends, and their impacts on students’ reading comprehension abilites. The findings reveal that guided reading strategies, KWL strategies, metacognitive strategies, cooperative learning, and text-based learning are the most frequently implemented strategies and have proven effective in improving elementary school students’ reading comprehension skills. These strategies enhance student engagement, text comprehension, and critical thinking skills. This study emphasizes that the implementation of active, systematic, and contextual learning strategies is essential for improving the quality of reading comprehension instruction in elementary schools.